The Role Of Penta Helix In The Development Of The Creative Industry In The Field Of Culinary In Bandar Lampung City - Niki Agus Santoso; Nur Efendi; Maulana Agung (Cita konsultindo, 2024)
Penta Helix is ​​a collaboration model involving five main actors: government, academics, industry players, community and media. In the context of developing the creative culinary industry in Bandar Lampung City, Penta Helix plays an important role in creating an ecosystem that supports innovation and growth. This research aims to explore how synergy between Penta Helix actors can facilitate the development of the culinary industry in this city.The methods used include literature studies, interviews with stakeholders, and secondary data analysis. The research results show that the active involvement of each Penta Helix actor can accelerate the development of the culinary industry through several mechanisms: policy support by the government, research and education from academics, product and marketing innovation by industry players, community involvement in culinary activities, as well as promotion and reporting by the media. The implications of this research show that to optimize the potential of the culinary creative industry in Bandar Lampung, good coordination between Penta Helix actors is needed, development of programs that involve all parties, and increased awareness and community participation. This research provides insight for policy makers, entrepreneurs and academics in designing more effective and integrated development strategies.